Comparison of Physical Properties of Different Varieties of Cotton - Malik, Mumtaz Hasan; Hussain, Tanveer (Biological Sciences - PJSIR, 2007)
Ni neteen varieties of cotton of di fferent countries of origin were subjected to tests for determi nation of ph ysical properties of fibre viz. , length (mm), length un i formity (%), short fibre index (SFI %), strength (g/tex), elongation (%), fi neness (M icronai re val ue), reflectance (Rd val ue) and yel lowness (+b val ue), usi ng the Uster HVI system. Egypt (G i za 70), Egypt (Giza 88), I ndia (MCU 5), USA (Elpaso), Egypt (Giza 86), Sudan (Barkat) and CJS (Sultop) had better overall fi bre length, strength and length uniformity %, and low SF! %. Pearson correlation of these physical properties was also determi ned. A strong positive correlation was found among fi bre length, strength and length uniformity whi le al l three of these properties exhibi ted a strong negati ve correlation with SF! %.